Intraoperative Extradural Hematoma - Benedek, Pedro (Cirugía del Uruguay, 1980)
An exceptional case of intraoperative extradural hematoma is described, produced by the perforation by one of the pins of the skull - fixation device of the paper - thin skull of an infant with cronic intracranial hypertension due to a craniopharyngioma.